Increased Binding of Specificity Protein 1 to the IL21R Promoter in B Cells Results in Enhanced B Cell Responses in Rheumatoid Arthritis - Dam, Elizabeth M.; Maier, Alison C.; Hocking, Anne M.; Carlin, Jeffrey; Ng, Bernard; Buckner, Jane H. (Frontiers in Immunology, 2018)
B cells are implicated in rheumatoid arthritis (RA) based on the presence of autoantibodies and the therapeutic response to B cell depletion. IL-21 has a significant role in B cell development and function. Here we assess B cell responses to IL-21 and the mechanisms responsible for altered IL-21R expression in RA. Flow cytometry of PBMC and cultured B cells was used to quantify protein and mRNA levels of IL-21R, IL-21 signaling through pSTAT3, specificity protein 1 (SP1) and to determine cytokine production (IL-6) and maturation status of B cells in RA and healthy control subjects. SP1 binding to the IL21R promoter region in B cells was assessed with ChIP-qPCR. We demonstrate an increase in IL-21R expression in total and memory B cells from RA subjects, which correlated with responsiveness to IL-21 stimulation. Stimulation of naïve RA B cells with IL-21 and CD40L resulted in an increase in differentiation into plasmablasts and an increase in IL-6 production in comparison to healthy controls, which was dose dependent on IL-21 stimulation. IL-21R expression on memory B cells in RA synovial fluid was comparable to peripheral blood making our study pertinent to understanding B cell responses in the joint and site of inflammation. We identified an increase in SP1 protein and mRNA in RA B cells and demonstrate an increase in binding of SP1 to the IL21R promoter region, which suggests a mechanism by which IL-21R expression is enhanced on B cells in RA. Taken together, our results indicate a mechanism by which IL-21 enhances B cell development and function in RA through an SP1 mediated increase in IL-21R expression on B cells.